2022
DOI: 10.3390/jcm11185264
|View full text |Cite
|
Sign up to set email alerts
|

High Mortality in an Older Japanese Population with Low Forced Vital Capacity and Gender-Dependent Potential Impact of Muscle Strength: Longitudinal Cohort Study

Abstract: Generally, weak muscle power is associated with high mortality. We aimed to evaluate the unknown association between % predicted value forced vital capacity (FVC% predicted) and mortality in asymptomatic older people, and the impact of muscle power on this association. We analyzed the Tsurugaya cohort that enrolled Japanese people aged ≥70 for 15 years with Cox proportional hazards model. Exposure variables were FVC% predicted and leg power. The outcome was all-cause mortality. The subjects were divided into q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…On the other hand, in women only the reduction of the percent predicted FVC was a mortality risk factor (HR = 1.67). In conclusion, a low percent predicted FVC was associated with high mortality and unfavorable effects of lower limb strength in men [19]. The results of the present study indicated that in older adults, a signi cant reduction in FVC, distance covered on the 6MWT, and limb strength was observed.…”
Section: Discussionsupporting
confidence: 56%
“…On the other hand, in women only the reduction of the percent predicted FVC was a mortality risk factor (HR = 1.67). In conclusion, a low percent predicted FVC was associated with high mortality and unfavorable effects of lower limb strength in men [19]. The results of the present study indicated that in older adults, a signi cant reduction in FVC, distance covered on the 6MWT, and limb strength was observed.…”
Section: Discussionsupporting
confidence: 56%
“…On the other hand, in women only the reduction of the percent predicted FVC was a mortality risk factor (HR = 1.67). In conclusion, a low percent predicted FVC was associated with high mortality and unfavorable effects of lower limb strength in men [ 22 ]. The results of the present study indicated that in older adults, a significant reduction in FVC, distance covered on the 6MWT, and limb strength was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed an association between muscle weakness and pneumonia (Komatsu et al, 2018 ; Miyatake et al, 2022 ; Okazaki et al, 2020 ; Shiokawa et al, 2023 ). As for the relationship between swallowing muscles and pneumonia, a previous study showed an association between low tongue pressure and the onset of pneumonia in stroke patients (Nakamori et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%